2003
DOI: 10.1002/app.12127
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of aqueous polyaniline dispersions by micellar‐aided polymerization

Abstract: Polyaniline (PAn) dispersed in water was prepared with sodium dodecylsulfonate (SDS) as a surfactant with varying concentrations of aniline and HCl and molar ratios of SDS/aniline. The PAn dispersion was homogeneous and stable, and its pH value could be adjusted. The conductivity of PAn powder, precipitated from this dispersion, was as high as 20 S/cm. The transmission electron microscopy morphology of PAn assembled in the dispersion was particle-like, fiber-like, or coil-like, depending on the initial concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(39 citation statements)
references
References 41 publications
1
35
0
1
Order By: Relevance
“…Accordingly, PANI nanostructures can be made by introducing ''structural directors'' into the chemical polymerization bath. These structural directors include ''soft templates'' such as surfactants, 16 organic dopants, 17 or polyelectrolytes 18 that assist in the self-assembly of PANI nanostructures. Kaner et al reported that by using relatively dilute aniline solutions, PANI nanofibers could be obtained when the oxidant was added at a single time, whereas only granular PANI particulates were formed when the oxidant was added dropwise.…”
Section: Synthesis and Characterization Of Tailor-made Panimentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, PANI nanostructures can be made by introducing ''structural directors'' into the chemical polymerization bath. These structural directors include ''soft templates'' such as surfactants, 16 organic dopants, 17 or polyelectrolytes 18 that assist in the self-assembly of PANI nanostructures. Kaner et al reported that by using relatively dilute aniline solutions, PANI nanofibers could be obtained when the oxidant was added at a single time, whereas only granular PANI particulates were formed when the oxidant was added dropwise.…”
Section: Synthesis and Characterization Of Tailor-made Panimentioning
confidence: 99%
“…3(e)]. 16 XRD of PANI-metal composites exhibited intense peaks corresponding to the same range for the aggregated PANI structure [ Fig. 3(a-d)].…”
mentioning
confidence: 91%
“…Nano-particles synthesized by PANI are also widely reported in literature as they are processable by dispersion in common organic solvents [11]. One dimensional nano-structures of PANI is being synthesized by chemical oxidative or electrochemical polymerization of monomer with the help of surfactant acting as a template, [17] whereas PANI nanorods and nanotubes have been synthesized without using any surfactant [8,18]. Formation of a cluster of hexagonal nanorods of PANI is also reported in literature [10] by using binary oxidants during its synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The previous methods for making polyaniline nanostructures usually require structure-directing templates, such as zeolite channels [26] or nanoporous membranes [27], surfactants [28], etc. These complex synthetic conditions require removal of the templates at the end of the reaction, resulting in low production rates.…”
Section: Methodsmentioning
confidence: 99%